2019
DOI: 10.1161/cir.0000000000000707
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Therapies for Acute Pulmonary Embolism: Current Status and Principles for the Development of Novel Evidence: A Scientific Statement From the American Heart Association

Abstract: Pulmonary embolism (PE) represents the third leading cause of cardiovascular mortality. The technological landscape for management of acute intermediate- and high-risk PE is rapidly evolving. Two interventional devices using pharmacomechanical means to recanalize the pulmonary arteries have recently been cleared by the US Food and Drug Administration for marketing, and several others are in various stages of development. The purpose of this document is to clarify the current state of endovascular interventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
357
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 332 publications
(366 citation statements)
references
References 121 publications
3
357
0
6
Order By: Relevance
“…During the COVID-19 pandemic, similar to other consultative services, PERTs should transition from in-person inpatient evaluation to e-consults using phone calls or telemedicine systems whenever feasible. It is important to note that, there are minimal available data demonstrating lower mortality from routine use of advanced VTE therapies (91,92). Therefore, the use of catheter-directed therapies during the current outbreak should be limited to the most critical situations.…”
Section: Covid-19 and Interventional Therapies For Vtementioning
confidence: 99%
“…During the COVID-19 pandemic, similar to other consultative services, PERTs should transition from in-person inpatient evaluation to e-consults using phone calls or telemedicine systems whenever feasible. It is important to note that, there are minimal available data demonstrating lower mortality from routine use of advanced VTE therapies (91,92). Therefore, the use of catheter-directed therapies during the current outbreak should be limited to the most critical situations.…”
Section: Covid-19 and Interventional Therapies For Vtementioning
confidence: 99%
“…(3) classification), thus attempting to clarify the question of anticoagulation during CDT while facilitating future comparisons and meta-analyses (13). The current study reports GUSTO-major (1.9%, including a single intracranial hemorrhage), GUSTO-moderate (1.9%), and GUSTO-minor (2.6%) complication rates that are similar (13,14) or lower (15,16) than those reported in studies using full therapeutic-dose anticoagulation (14,15), the GUSTO (16) classification, and in a meta-analysis (13). The SEATTLE II trial (16), the largest CDT trial to use GUSTO criteria, reported 0.7% GUSTO-major complications (1 groin Final systolic PAP (mmHg) 42.5 ± 11.6 42.5 ± 11.9 42.5 ± 11.5 .9…”
Section: Discussionmentioning
confidence: 99%
“…These teams now have access to a wide variety of US Food and Drug Administration 510(k)-cleared devices (nine to be exact) to treat PE from an interventional perspective. 5 One increasingly used modality for the treatment of intermediate-high and high-risk PE is infusion of a thrombolytic agent via a catheter inserted into the pulmonary artery (known as catheter-directed thrombolysis [CDT]). 5,6 One device, the 5F catheterbased EkoSonic endovascular system (EKOS Corporation), is cleared by the US Food and Drug Administration for acute PE therapy and is an ultrasound-assisted thrombolytic (CDT-US) alternative to simple delivery of thrombolytic agents via a multi-holed infusion catheter.…”
mentioning
confidence: 99%
“…5 One increasingly used modality for the treatment of intermediate-high and high-risk PE is infusion of a thrombolytic agent via a catheter inserted into the pulmonary artery (known as catheter-directed thrombolysis [CDT]). 5,6 One device, the 5F catheterbased EkoSonic endovascular system (EKOS Corporation), is cleared by the US Food and Drug Administration for acute PE therapy and is an ultrasound-assisted thrombolytic (CDT-US) alternative to simple delivery of thrombolytic agents via a multi-holed infusion catheter. The addition of focused ultrasound energy to traditional CDT aims to disrupt thrombus ultrastructure, allowing for more effective penetration of thrombolytic molecules into a thrombus.…”
mentioning
confidence: 99%
See 1 more Smart Citation